2008
DOI: 10.4161/auto.5774
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer agent siramesine is a lysosomotropic detergent that induces cytoprotective autophagosome accumulation

Abstract: A σ-2 receptor ligand siramesine induces lysosomal leakage and cathepsin-dependent death of cancer cells in vitro and displays potent anti-cancer activity in vivo. The mechanism by which siramesine destabilizes lysosomes is, however, unknown. Here, we show that siramesine induces a rapid rise in the lysosomal pH that is followed by lysosomal leakage and dysfunction. The rapid accumulation of siramesine into cancer cell lysosomes, its ability to destabilize isolated lysosomes, and its chemical structure as an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
120
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(141 citation statements)
references
References 38 publications
12
120
0
3
Order By: Relevance
“…Under physiological conditions, these proteases are found within the lysosomes but are released into the cytoplasm upon exposure to cell damaging agents, thereby triggering a cascade of intracellular events leading to cell death. The σ 2 selective ligand siramesine has been reported to cause lysosomal leakage and induce cell death by caspase-independent mechanisms [41,45]. The localization of fluorescent σ 2 receptor probes in the lysosomes is consistent with the hypothesis that siramesine induces cell death partially by targeting lysosomes to cause lysosomal damage, the release of proteases, and eventually cell death.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Under physiological conditions, these proteases are found within the lysosomes but are released into the cytoplasm upon exposure to cell damaging agents, thereby triggering a cascade of intracellular events leading to cell death. The σ 2 selective ligand siramesine has been reported to cause lysosomal leakage and induce cell death by caspase-independent mechanisms [41,45]. The localization of fluorescent σ 2 receptor probes in the lysosomes is consistent with the hypothesis that siramesine induces cell death partially by targeting lysosomes to cause lysosomal damage, the release of proteases, and eventually cell death.…”
supporting
confidence: 68%
“…Several studies have shown that σ 2 ligands induced cell death. The proposed mechanisms of cell death include caspase-independent apoptosis [40], lysosomal leakage [41], Ca 2+ release [42,43], oxidative stress [41], ceramide production [44] and autophagy [45]. However, the subcellular localizations where the σ 2 ligands bind and function were not known.…”
Section: Confocal and Two Photon Microscopy Studies Of σ 2 Receptors mentioning
confidence: 99%
“…The data presented above add BAMLET to the growing list of cytotoxic agents that can induce a nonapoptotic lysosomal cell death pathway (35). In light of these data, combination therapies with agents further sensitizing cells to lysosomal destabilization (such as microtubule disturbing drugs vincristine and paclitaxel) as well as with those inducing lysosomal destabilization (such as siramesine) should be experimentally tested (38,39). Given that many cancers have fundamental defects in both mitochondrial and death receptor signaling pathways, and that these apoptotic defects specifically characterize the most aggressive therapy resistant tumors, BAMLET alone or in combination therapies may provide new treatment options in aggressive cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is noteworthy that the linkage from autophagy to LMP is not always unidirectional. In this regard, some lysosomotropic detergents, such as siramesine, which trigger cell death via a direct destabilization of lysosomes, have been shown to induce cytoprotective accumulation of autophagosomes (Ostenfeld et al, 2008).…”
Section: Extent Of Autophagymentioning
confidence: 99%